Poetic Formula “I see” in K. N. Batyushkov’s Work: Creative Assimila-tion of the Derzhavin Tradition - K. A. Potashova (Научный диалог, 2020)
The author analyses the visual metaphors of K. N. Batyushkov’s poetry, in which he acts as the creative heir to the artistic style of G. R. Derzhavin. The urgency of the problem is connected with the need to clarify the features of the creative method of K. N. Batyushkov in the aspect of his assimilation of the Derzhavin tradition. The novelty of the research is connected with the expansion of ideas about the poetics of the visual in Russian poetry of the early 19th century, in particular, in the work of K. N. Batyushkov. It is proved that K. N. Batyushkov represents vision as a process of cognition of the world. The mechanisms of K. N. Batyushkov’s transformation of visually perceived world in an artistic image are considered, the artistic thinking of the poet is reconstructed. It is revealed that the model of creating a visual verbal image in K. N. Batyushkov’s work is based on the poetic formula “I see.” It is shown that K. N. Batyushkov emphasizes the position of the observer, reflecting at the same time on the diversity and greatness of God’s world, on the cause-and-effect relationship of reality phenomena. It is established that a special place is given to the representation of historical events in the work of the poet: through the poetic formula “I see” K. N. Batyushkov places himself inside the picture, which corresponds to the emerging aesthetics of romanticism with its cult of personal perception of reality.